Efecto de la fibra insoluble y soluble en las células caliciformes productoras de mucinas en cuyes post destete - Guevara Zari, Alejandra Estefania (2024)
Dietary fiber is crucial for intestinal health and the function of mucin-producing goblet cells that protect the intestinal epithelium. This research evaluated the effects of soluble and insoluble dietetic fiber on these cells in post-weaning guinea pigs. For this purpose, we randomly distributed 32 15-day-old Type A1 weaned guinea pigs in four treatments formulated with different degrees of soluble fiber (SF) and insoluble fiber (IF). Diet 1 was low in SF (4.48%) and IF (29%); Diet 2 was high in SF (12%) and low in IF (28.0%); Diet 3 was low in SF (6.52%) and high in IF (35.5%); and diet 4 with high SF (12.0%) and IF (35.8%). We fed the animals with the diets for ten days and subsequently took jejunum samples. Using histological and histochemical techniques, we determined the number of goblet cells with acid mucins (Alcian Blue pH 2.5) and neutral mucins (Periodic Acid-Schiff) in crypts and intestinal villi. The number of acidic and neutral goblet cells was higher in diets containing high levels of insoluble fiber, which influenced an increase in the number of goblet cells with neutral mucins in intestinal crypts (p = 0.0100). In contrast, increasing the level of soluble fiber showed a tendency (p = 0.100) to reduce the number of these cells in crypts. We detected no significant difference in the effect of soluble and insoluble fiber and their interaction on acid mucins.